The Unchanging Word vs. Evolving Science: The Trial of Human Belief - Muhammad Owais Isaac (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research paper advocates for the Islamic perspective of creationism, asserting that all life is intentionally designed by Allah (SWT), in direct contrast to Darwinian evolutionary theory, which erroneously proposes that life arises from random processes and natural selection. The Quranic narrative provides comprehensive insights into the creation of human beings and the universe, with multiple verses explicitly detailing the divine process of creation. While contemporary scientific methodologies offer insights into biological mechanisms, they fundamentally fail to explain the profound metaphysical dimensions of life's origin and the intricate divine design evident in creation. The Quranic perspective emphasizes that Allah is the ultimate Creator (Khaliq), Who designs with precise purpose and wisdom. This study critically examines the philosophical and theological implications of accepting Darwinian interpretations, arguing that such theories fundamentally undermine the belief in purposeful, divine creation. By integrating principles from biology, thermodynamics, and quantum mechanics through an Islamic epistemological lens, this research illustrates how scientific laws and biological mechanisms can be understood as manifestations of divine wisdom rather than products of mere chance. Ultimately, this research emphasizes that belief in purposeful creation provides a comprehensive, spiritually grounded framework for understanding human existence, challenging atheistic scientific narratives that neglect the profound spiritual dimensions of creation.